Catalytically Active Bacterial Nanocellulose‐Based Ultrafiltration Membrane. Issue 15 (8th March 2018) - Xu, Ting; Jiang, Qisheng; Ghim, Deoukchen; Liu, Keng‐Ku; Sun, Hongcheng; Derami, Hamed Gholami; Wang, Zheyu; Tadepalli, Sirimuvva; Jun, Young‐Shin; Zhang, Qinghua; Singamaneni, Srikanth
Abstract: Large quantities of highly toxic organic dyes in industrial wastewater is a persistent challenge in wastewater treatment processes. Here, for highly efficient wastewater treatment, a novel membrane based on bacterial nanocellulose (BNC) loaded with graphene oxide (GO) and palladium (Pd) nanoparticles is demonstrated. This Pd/GO/BNC membrane is realized through the in situ incorporation of GO flakes into BNC matrix during its growth followed by the in situ formation of palladium nanoparticles. The Pd/GO/BNC membrane exhibits highly efficient methylene orange (MO) degradation during filtration (up to 99.3% over a wide range of MO concentrations, pH, and multiple cycles of reuse). Multiple contaminants (a cocktail of 4‐nitrophenol, methylene blue, and rhodamine 6G) can also be effectively treated by Pd/GO/BNC membrane simultaneously during filtration. Furthermore, the Pd/GO/BNC membrane demonstrates stable flux (33.1 L m −2 h −1 ) under 58 psi over long duration. The novel and robust membrane demonstrated here is highly scalable and holds a great promise for wastewater treatment. Abstract : A novel and scalable filtration membrane is introduced for highly efficient organic dye‐contaminated wastewater treatment. The membrane is comprised of in situ grown bacteria nanocellulose (BNC) and graphene oxide (GO) and in situ formed palladium nanoparticles. The process and design can be easily adapted to realize other GO/BNC‐based functional membranes with potential applications in catalysis, separations, energy storage, and environmental remediation.